Detection of donor-derived cell-free DNA in the setting of multiple kidney transplantations - Pettersson, Linnea; Frischknecht, Lukas; Westerling, Sofia; Ramezanali, Hamid; Weidmann, Lukas; Lopez, Kai Castrezana; Schachtner, Thomas; Nilsson, Jakob (Frontiers in Immunology, 2024)
Background: The routine use of donor derived cell free DNA (dd-cfDNA) assays to monitor graft damage in patients after kidney transplantation is being implemented in many transplant centers worldwide. The interpretation of the results can be complicated in the setting of multiple sequential kidney transplantations where accurate donor assignment of the detected dd-cfDNA can be methodologically challenging. Methods: We investigated the ability of a new NGS based dd-cfDNA assay to accurately identify the source of the detected dd-cfDNA in artificially generated samples as well as clinical samples from 31 patients that had undergone two sequential kidney transplantations. Results: The assay showed a high accuracy in quantifying and correctly assigning dd-cfDNA in our artificially generated chimeric sample experiments over a clinically meaningful quantitative range. In our clinical samples, we were able to detect dd-cfDNA from the first transplanted (non-functioning) graft in 20% of the analyzed patients. The amount of dd-cfDNA detected from the first graft was consistently in the range of 0.1-0.6% and showed a fluctuation over time in patients where we analyzed sequential samples.